Identification of a novel role for Drosophila MESR4 in lipid metabolism. (30th January 2015) - Tsuda‐Sakurai, Kayoko; Seong, Ki‐Hyeon; Horiuchi, Junjiro; Aigaki, Toshiro; Tsuda, Manabu
<x xml:space="preserve">Abstract</x> Drosophila provides a powerful genetic model to analyze lipid metabolism. Drosophila has an adipose‐like organ called the fat body, which plays a crucial role in energy homeostasis. Here, we conducted a fat body‐specific misexpression screen to identify genes involved in lipid metabolism. We found that over‐expression of a nuclear protein with nine C2H2 type zinc‐finger motifs and a PHD‐finger, Misexpression suppressor of ras 4 (MESR4), reduces lipid accumulation in the fat body, whereas MESR4 knockdown increases it. We further show that MESR4 up‐regulates the expression of major lipases, which may account for the reduction in lipid storage in the fat body and the release of free fatty acids (FFAs) in the body. These results suggest that MESR4 acts as an important upstream regulator of energy homeostasis.